STUDENTS’ CRITICAL THINKING IN ONLINE DISCUSSION FORUM - Sela Fitriana; Helta Anggia (Bandar Lampung University (UBL), 2016)
Online discussion forum is well-known in educational technology development especially in blended learning because it supports the traditional face to face (f2f) class. Online discussion forum is familiar as the leading of critical thinking process. This paper reports about qualitative study on web-based class by using blended learning focuses on online discussion forum. This study is held in order to analyze the critical thinking process that appears during online discussion forum class. This study is conducted with 26 students of speaking class of Bandar Lampung University. Observation and questionnaire are conducted to see critical thinking process during online discussion forum class. The finding of the study will help the further study to develop critical thinking ability.